Consequences of Folding the Mitochondrial Inner Membrane - Mannella, Carmen A. (Frontiers in Physiology, 2020)
A fundamental first step in evolution of eukaryotes was infolding of the chemiosmotic membrane of the endosymbiont. This allowed the proto-eukaryote to amplify ATP generation while constraining the volume dedicated to energy production. Infolding of the inner membrane is not random but rather creates specialized compartments (cristae) tuned for optimum bioenergetic function. Membrane infolding also presents complications in terms of generating the folds and maintaining mitochondrial integrity in response to stresses. This review describes mechanisms that have evolved to regulate inner membrane topology and either preserve or, when appropriate, rupture the outer membrane.